ChemInform Abstract: Marine Natural Products. Issue 34 (August 2015) - Blunt, John W.; Copp, Brent R.; Keyzers, Robert A.; Munro, Murray H. G.; Prinsep, Michele R.
Abstract Review: literature published in 2013; 982 refs.